GFRP sandwich composite with PET core in shell structure of footbridge - Chróścielewski, Jacek; Klasztorny, Marian; Miśkiewicz, Mikołaj; Pyrzowski, Łukasz; Rucka, Magdalena; Wilde, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper presents experimental study of sandwich composite used for an innovative foot-and-cycle bridge. The footbridge has a U-shaped shell structure made of sandwich consisting GFRP laminate covers and foam PET core. The bridge is manufactured using the infusion technology. Results of one and two directional tension tests of the laminates, compression tests of PET foam samples and 3-point as well as 4-point bending tests of sandwich beams are presented.